Choosing inequality: how economic security fosters competitive regimes - Alexander Lenger; Stephan Wolf; Nils Goldschmidt (The Journal of Economic Inequality, 2020)
In a novel experimental design, we study how social immobility affects the choice among distributional schemes in an experimental democracy. We design a two-period experiment in which subjects first choose a distributional scheme by majority voting (“social contract”). Then subjects engage in a competitive real-effort task to earn points. Based on production success, participants are ranked from best to worst. In combination with the initially chosen scheme, these ranks determine the final payout of the first round, leading to a pattern of societal stratification. Participants are informed individually about points and rank, before the same sequence of voting, production and payoff determination is repeated in a second round. To test the effect of social immobility on choosing distributional regimes the experiment is conducted with and without a social immobility factor, i.e. a different weighting of the two rounds. In our standard scenario, payoffs are simply added. In our “social immobility setting”, we alter the game as follows: the actual income in round 2 is calculated by adding 0.2 times the raw payoff from the second production game and 0.8 times the income from round 1. With the higher importance of round 1 success, we simulate the fact that economic movement upwards and downwards in societies (“social mobility”) is a de facto rigid constraint: high and low incomes tend to reproduce themselves. Our main findings are that in the Equal Weight Treatment, most groups opt for complete equality in both rounds, while in the unequal weight setting the initial choice of equality is followed by a shift to the most competitive regime. In both treatments, we observe that those performing well in round 1 tend to vote for unequal schemes in round 2, while low-performers develop an even stronger “taste for equality”. This supports a central Rawlsian idea: behind an (experimental) “veil of uncertainty”, the lack of idiosyncratic information is strong enough to let people decide as if driven by social preferences. The different group decisions in round 2 suggest that for this to happen, stakes need to be sufficiently high. To our surprise, other factors like gender, social background or real-life income have hardly any impact on unveiled decision making. We conclude that in our experimental democracy, competition based income allocation (a “market economy”) finds support only if people are sufficiently well off. Hence, increasing inequality perpetuated by social immobility is likely to undermine the general support for market-based systems.
Keywords: C91; C92; D31; D63; D71; D81; D90; 300; Decision making; Experiment; Inequality; Information; Justice; Social choice; Social contract; Social immobility; Stratification